Thermophysical behaviour of biofuel under detonation combustion - Ismail, Izham Izzat; Mohd Yusof, Muhammad Fadzrulizwan; Azami, Muhammad Hanafi; Mohd Ihsan, Ahmad Ariffin (2020)
The purpose of this research is to assess biofuel on thrust behaviour and the propulsive performance of ideal Pulse Detonation Engines (PDEs) based on the parametric cycle of analysis for supersonic heat addition. Detonative combustion utilises shocks and detonation waves by providing pressure-rise combustion and prominently result in higher propulsive and thermodynamic efficiency as compared to conventional isobaric heat addition in a Brayton cycle combustor. This research uses the numerical approach to calculate the performance of aircraft by changing the ambient condition. Furthermore, this research chose to study two biofuels; Bioethanol and Babassu Biokerosene BBK100. Both biofuels have been used in the conventional air-breathing engine. The researchers in this study examined the performance of the fuels by observing the pressure, Mach number, temperature, and density ratios. The condition of the mass flux varied from 3500kg⁄sm^(-2) to 9400kg⁄sm^(-2) while the initial temperature varied from 200K up to 790K, due to the characteristics of Bioethanol and Babassu Biokerosene BBK100, there are differences in detonation velocity, propulsive efficiency, and thermodynamic efficiency. Babassu Biokerosene BBK100 has better detonation velocity as compared to Bioethanol, which is 1900.4 m/s. Hence, the result shows that biofuel is feasible for the Pulse Detonation Engines (PDEs) as it brings due improvement to aircraft performance.